When Did We Begin to Spell ""Heteros*edasticity"" Correctly? - Alfredo R. Paloyo (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Using digitized texts scanned by Google and subjected to optical character recognition, I show that heteroskedasticity overtook heteroscedasticity as the preferred spelling in 2001 and has continued to dominate, except for 2005, up to 2008. The latest trends indicate that writers are moving toward the k variant. However, for words such as homoskedasticity, heteroskedastic, and homoskedastic, the corresponding spellings using c are still overwhelmingly dominant, albeit slowly shifting. – – Unter Verwendung von Texten, die durch Google digitalisiert und einem Texterkennungsprogramm unterzogen wurden, zeige ich, dass sich heteroskedasticity gegenüber heteroscedasticity 2001 als bevorzugte Schreibweise durchsetzte und, mit Ausnahme von 2005, bis 2008 weiterhin vorgeherrscht hat. Die aktuellen Entwicklungen deuten darauf hin, dass Verfasser vermehrt die k-Schreibweise verwenden. Allerdings ist für Wörter wie homoskedasticity, heteroskedastic und homoskedastic die Schreibweise mit c immer noch deutlich stärker verbreitet, wenngleich auch hier ein langsamer Wandel stattfindet.
Keywords: A20; B19; B29; 330; Heteroskedasticity; Culturomics; Google Books; econometric orthography; philology; Heteroskedasticity; Culturomics; Google Books; econometric orthography; philology